STRATEGI BISNIS PT XYZ PADA INDUSTRI FUEL RETAIL DI DKI JAKARTA DAN BANTEN - Rafdi Dzulfikar Ramdhani; Lukman M. Baga; Popong Nurhayati (School of Business, Bogor Agricultural University (SB-IPB), 2021)
PT XYZ is a company engaged in the retail business of Pertamina's products. PT XYZ needs to have the right alternative strategy to respond the slowdown in fuel sales growth and the growth of foreign gas stations in DKI Jakarta & Banten fuel retail industry. This research aims to analyze internal and external factors that affect the business of PT XYZ and develop appropriate business strategies for PT XYZ. Some of the analytical tools used in this research are VRIO analysis, Porter's Five Forces, PESTEL, Internal-External matrix, and SWOT analysis. The method of collecting data is carried out through observation, interviews, questionnaires, and literature studies. Interviewees in this study consisted of internal parties that government policies in PT XYZ and external parties, namely the BPH Migas committee. Based on the results of the identification of the internal and external environment, there are several internal factors consisting of 7 strengths and 5 weaknesses of the company, as well as strategic external factors consisting of 4 opportunities and 4 threats that affect the business of PT XYZ. PT XYZ is in quadrant V in the IE matrix, so that there are 9 alternative strategies that can be applied to PT XYZ's business, consisting of 6 product development strategies and 3 market penetration strategies. Keywords: alternative strategy, PESTEL, Porter’s Five Forces, SWOT, VRIO